The Effect of Intellectual Capital on Financial Performance through Competitive Advantage as an Intervening Variable (Empirical Study on the Banking Industry Listed on the IDX 2025) - Widy Hastuty HS; Amin Hou; Duffin Duffin; Laily Ramadhani; Dominggus Sijauta (International Journal of Science and Environment (IJSE), 2025)
This study aims to analyze the effect of Intellectual Capital on Financial Performance with Competitive Advantage as a mediating variable in banking companies listed on the Indonesia Stock Exchange for the period 2022-2024. The research method used is quantitative with a population of 42 banking issuers, while the sample is determined by purposive sampling so that 11 issuers meet the criteria. Secondary data in the form of annual reports were obtained from the official websites of each bank and the Indonesia Stock Exchange. The analysis technique used is Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results showed that Intellectual Capital has a positive and significant effect on Financial Performance, Intellectual Capital has a positive and significant effect on Competitive Advantage, and Competitive Advantage has a positive and significant effect on Financial Performance. In addition, Intellectual Capital also has an indirect positive effect on Financial Performance through Competitive Advantage as a mediating variable. These findings indicate that strengthening Intellectual Capital can increase competitive advantage which in turn encourages operational efficiency and financial performance of banks.